DETERMINAN MANAJEMEN LABA DALAM PERUBAHAN TARIF PAJAK PENGHASILAN BADAN - Suando, Santoso; Pikir, Toto Warsoko; Lasdi, Lodovicus (Widya Mandala Surabaya Catholic University, 2013)
In 2008, the Indonesian Directorate General of Tax Law changes the Income Tax Law. They have been issued the Law Division 36 of 2008 on Income Tax. Corporate income tax rates changes from progressive rates to single rate, which 28% were effected in 2009 and 25% were effected in 2010. The purpose of this research is to examine and analyze whether changes in corporate income tax rates in Indonesia responded to earnings management by comparing the level of discretionary accruals in the period before and after the enactment of Law Division 36 of 2008. Another purpose of this research is to test whether tax incentives (tax planning and net de-ferred tax liabilities) and non-tax incentives (earnings pressure, level of debt, firm size, and managerial ownership) affect earnings management. This research is quantitative research with the object of research is manufacturing firms listed on the Indonesia Stock Exchange from 2006 to 2011. Data obtained from the publication of the audited financial report or annual report and ICMD. Sampling in this research is purposive sampling. Data analysis techniques used in this research are different test and multiple linear regression analysis. The results showed that there is no management responded by conducting earnings management when corporate income tax rates in Indonesia has changed. Regression results indicate that tax incentives (tax planning and net deferred tax liabilities) and non-tax incentives (earnings pressure, the level of debt and managerial ownership) have a significant effect on earnings management. For firm size had no significant effect on earnings management.